1983
DOI: 10.1007/bf02916619
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the major elements and trace elements of 10 methanogenic bacteria determined by inductively coupled plasma emission spectrometry

Abstract: The elemental composition of 10 methanogenic species was determined by inductively coupled plasma emission spectrometry and by a C-H-N-analyzer. The 10 species were representative of all three orders of the methanogens and were cultivated under defined conditions. Special emphasis was given toMethanosarcina barkeri, represented by 5 strains and cultivated on various substrates. The following elements with the lowest and highest values in parentheses were determined: C (37-44%, w/w), H (5.5-6.5%), N (9.5-12,8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
6
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(90 citation statements)
references
References 33 publications
6
77
6
1
Order By: Relevance
“…However, the cellular zinc content of of methanogens is higher in the species that utili2 and zinc concentrations are positively correlate molybdenum content of the formate-utilizing species (29 …”
Section: Discussionmentioning
confidence: 90%
“…However, the cellular zinc content of of methanogens is higher in the species that utili2 and zinc concentrations are positively correlate molybdenum content of the formate-utilizing species (29 …”
Section: Discussionmentioning
confidence: 90%
“…Zinc is often adventitiously bound during purification of proteins. However, zinc is present at high concentrations (50 to 630 ppm) in methanogens (34) and has been found in formate dehydrogenase (33) and F420-non-reactive hydrogenase (1) of M. formicicum. Selenium was not found in the enzyme from M. formicicum and has only been reported present in the F420-hydrogenases from M. vannielii (41) and M. voltae (27).…”
Section: Discussionmentioning
confidence: 99%
“…As in Fe concentrations, in the concentrations of Ni, Co and W an increase was measured due to the additives in the present study. In a previous study with 10 species of methanogens, the composition of them was observed to vary quite a bit (Scherer et al 1983). Methanogens were seen to consist of C (37-44 % WW), H (5.5-6.5 %), N (9.5-12.8 %), Na (0.3-4.0 %), K (0.13-5.0 %), S (0.56-1.2 %), P (0.5-2.8 %), Ca (85-4500 ppm), Mg (0.09-0.53 %), Fe (0.07-0.28 %), Ni (65-180 ppm), Co (10-120 ppm), Mo (10-70 ppm), Zn (50-630 ppm), Cu (<10-160 ppm), and Mn (<5-25 ppm, Scherer et al 1983).…”
Section: Additives To Improve Anaerobic Digestion Of Pig Slaughterhoumentioning
confidence: 97%